Konstruksi Sosial Masyarakat terhadap Berita Hoaks melalui Media Sosial Whatsapp pada Masa Kampanye Pemilu 2024 - Fadila, Helya (Huma: Jurnal Sosiologi, 2025)
The phenomenon of hoax news dissemination is a recurring social issue in society, including in the Telaga Biru Sub-district. This study aims to examine how the community in Telaga Biru constructs social meaning regarding hoax news during the 2024 election campaign, particularly as disseminated through the social media platform WhatsApp. This research employs a qualitative method with a phenomenological approach. The theoretical framework used is the social construction theory by Peter L. Berger and Thomas Luckmann. Data were collected through semi-structured interviews and documentation. The data analysis process involved three stages: data reduction, data presentation, and conclusion drawing. The findings show that the social construction of hoax news among residents of Telaga Biru aged 35 to 65 has changed in terms of interpretation and response, influenced by their actions and interactions on WhatsApp during the 2024 election campaign. Previously, they tended to believe in and be influenced by such news, often struggling to distinguish between factual and false information. However, they have now developed a more critical mindset and are capable of verifying information before accepting or spreading it. This study contributes to a deeper understanding of the dynamic relationship between local values and politics. It also serves as a reference for digital literacy efforts and public communication policies in addressing the spread of hoaxes during election campaigns. Further research is recommended to explore the community’s social construction of hoax news using other social media platforms or from different theoretical perspectives.